Enhanced Luminescent Properties of Europium Complex by Replacement of Water Molecules by 1,10-Phenanthroline - Kumar, Rajesh; Arora, Rajni; Taxak, V.B.; Khatkar*, S.P. (Asian Journal of Chemistry, 2014)
The complex [Eu(L)3(phen)] (where L = 2'-hydroxy-4'-methoxy-2-phenylacetophenone, phen = 1,10-phenanthroline) was synthesized and characterized, by elemental analysis, energy dispersive X-ray spectroscopy, 1H NMR spectroscopy infra red spectroscopy, TGA/DTA, scanning electron microscopy and the excitation as well as emission spectrum. The [Eu(L)3(phen)] had regular shaped particles with size less than 1 μm without any phase separation and on excitation at 344 nm emits bright red luminescence with main peak at 614 nm. The complex emitting red luminescence might be used to make the electroluminescent devices for display purposes.